ANALISIS METODE DAN MANFAAT PENDALAMAN KITAB SUCI PADA KELOMPOK KERASULAN KITAB SUCI EMAUS JOURNEY JALAN GODEAN YOGYAKARTA - Samosir, Bofry Wahyu; Tanureja, Indra (Bahasa Indonesia, 2025)
This study analyzes the methods and benefits of Bible study for Christian believers. Studying the Bible provides many benefits in the life journey of Christian believers. Still, the various challenges and difficulties that believers face in finding meaning in the Bible's text, as well as the unstructured interpretation methods, often become obstacles to obtaining these benefits. This study uses a qualitative descriptive method with a survey approach to eight (8) Emmaus Journey Bible Apostolate group members in Jalan Godean, Yogyakarta. Data were collected through a questionnaire containing several written questions about the interpretation method, benefits, and meanings obtained after studying the Bible. The study results show that studying the text of the Bible not only brings people closer to the Bible but also improves the quality of believers' understanding regarding the Bible and increasingly enables believers to live according to the Word of God in everyday life. In this case, believers need to use the right methods and approaches to interpret the text of the Bible according to its literary form and type. Some methods and approaches that can be used are the interpretation method in Dei Verbum 12, the historical-critical method, the narrative method, the sociological approach, the cultural anthropology approach, the psychological and psychoanalytic approach, and the allegorical approach. This study concludes that the study of the Bible has a great opportunity to help Christian believers explore the spiritual riches in the Bible, as long as the believers can interpret the texts in the Bible with the right methods and approaches and based on the three meanings of the texts in the Bible, namely the literal meaning, the spiritual meaning, and the deeper meaning. Recommendations are given to the Bible’s apostolate group to develop the methods and approaches to interpreting the texts of the Bible.